1993
DOI: 10.1007/bf01342694
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady interaction of a sphere with atmospheric temperature inhomogeneity at supersonic speed

Abstract: The structure of the shock layer and the abrupt aerodynamic forces acting on a sphere moving in an atmosphere with inhomogeneous inclusions of various shapes are considered.Inhomogeneities of the medium, through which a body moves at supersonic speed, can produce considerable changes in the shape and structure of the leading shock wave. The motion of a sphere through a plane inhomogeneity was studied in various aerodynamic formulations in [1--8]. In [1--3] the problem of the penetration of blunt axisymmetric b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…The principal effect of the interaction of a microwave-generated plasma with the flowfield surrounding a blunt body is thermal, that is, the effect of the interaction of a finite heated region with the flowfield structure (e.g., shock waves, expansions) generated by the aerodynamic body. Validation of this statement is provided by numerous ideal gas simulations (e.g., Georgievsky and Levin [9], Azarova et al [10], Farzan et al [11]) which have demonstrated drag reduction for the interaction of a finite heated region with a blunt body. However, in ideal gas simulations, the amount of energy deposited in the flowfield is parameterized by an assumed initial spatial distribution of thermodynamic properties (i.e., translational-rotational temperature and density) and velocity in a finite spatial region.…”
Section: A N Bmentioning
confidence: 97%
“…The principal effect of the interaction of a microwave-generated plasma with the flowfield surrounding a blunt body is thermal, that is, the effect of the interaction of a finite heated region with the flowfield structure (e.g., shock waves, expansions) generated by the aerodynamic body. Validation of this statement is provided by numerous ideal gas simulations (e.g., Georgievsky and Levin [9], Azarova et al [10], Farzan et al [11]) which have demonstrated drag reduction for the interaction of a finite heated region with a blunt body. However, in ideal gas simulations, the amount of energy deposited in the flowfield is parameterized by an assumed initial spatial distribution of thermodynamic properties (i.e., translational-rotational temperature and density) and velocity in a finite spatial region.…”
Section: A N Bmentioning
confidence: 97%
“…The first minimum in the curves is caused by a rarefaction wave reflection which is generated at the very beginning of the interaction process (see [8]). This rarefaction wave is an element of the solution of the Riemann problem which describes the interaction of the boundary of the heated area with the bow shock.…”
Section: A Study Of the Stagnation Pressure And Frontal Drag Force Fomentioning
confidence: 99%
“…Energy sources of different types (microwave, laser, discharge) were used for these purposes [6,7]. Two mechanisms have been established causing this phenomenon, the reflection of a rarefaction wave from the body's surface [8] and the effect of a vortex structure generating via the interaction of an energy source with a bow shock [6]. The latter effect was named the vortex drag reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Unsteady Energy Deposition 1. Levin (1993, 2004) Georgievskii and Levin [52] performed a series of Euler simulations at M 1 3 for the interaction of a thermal spot of various configurations with a sphere. The thermal spot originated upstream of the blunt body shock and was defined by a region of uniform reduced density s of the shape Fig.…”
Section: Georgievskii and Levin (2003)mentioning
confidence: 99%